-6=6(w-9)

Simple and best practice solution for -6=6(w-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6=6(w-9) equation:


Simplifying
-6 = 6(w + -9)

Reorder the terms:
-6 = 6(-9 + w)
-6 = (-9 * 6 + w * 6)
-6 = (-54 + 6w)

Solving
-6 = -54 + 6w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-6w' to each side of the equation.
-6 + -6w = -54 + 6w + -6w

Combine like terms: 6w + -6w = 0
-6 + -6w = -54 + 0
-6 + -6w = -54

Add '6' to each side of the equation.
-6 + 6 + -6w = -54 + 6

Combine like terms: -6 + 6 = 0
0 + -6w = -54 + 6
-6w = -54 + 6

Combine like terms: -54 + 6 = -48
-6w = -48

Divide each side by '-6'.
w = 8

Simplifying
w = 8

See similar equations:

| 7+78m=39m+25 | | 2x-2+3x+12=12x+6 | | -10(s+3)=-51 | | x^2+0.714x-0.153=0 | | -(c-10)=3 | | 5x+14=-49-4x | | 3x-6/12=10 | | 5(t+5)=5 | | x+6=3(4-x) | | 2/3x=-48 | | X^2+14+y^2+2y=14 | | -24+a=-38 | | fx=x^2-8x+67 | | y-5=-3(x+7) | | ln(2+sinx)=0 | | 6x+9=90 | | 3x-3+4x+8=12x+12 | | -26+2=-39+13x | | -21=2x-7 | | 1744/240 | | 6(4s+6)=228 | | 2m^2-20m+25=0 | | tan(x)= | | 6(x-8)+8=4(x-7) | | y+7=-3(x-5) | | X^2tanx= | | ln(5x-6)-2lnx=0 | | 150-2x=10 | | n^2+10=131 | | 16*sin^2(2t)+9+16cos^2(2t)=0 | | 5(2l+7)=105 | | -4x+31=3(1-3x)-2 |

Equations solver categories